DIVERSIFICATION OF THE TOURIST ATTRACTIVENESS OF COASTAL COMMUNES IN THE WEST POMERANIAN VOIVODESHIP (Research Bulletins of the Faculty of Economic Sciences, 2021)
The main aim of the research was to determine the differentiation of tourist attractiveness of coastal communes in the West Pomeranian Voivodeship. The time scope of the analysis covers data from 2018. In the field of research methods, the rank method was used. The data comes from secondary sources, such as: literature on the subject, data from the Central Statistical Office and Internet resources. To determine the level of tourist attractiveness of the surveyed communes, the indicators of tourism development were used, as well as indicators of sightseeing values and transport accessibility, i.e. the Baretje-Defert index, the accommodation density index, the percentage of legally protected areas, the number of cultural events organized in coastal communes, diversification seashore length, location in front of national roads, percentage of railway areas. As a result of the analyzes, the assumption was confirmed that, despite the well-developed tourist function, the coastal communes of the West Pomeranian Voivodeship are diversified in terms of tourist attractiveness.
Keywords: tourist attractiveness, coastal communes, West Pomeranian Voivodeship